PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU (Vigna radiata L ) DIBAWAH NAUNGAN DAN TANPA NAUNGAN DI DESA CAMPLONG II KECAMATAN FATULEU KABUPATEN KUPANG - Marlin Florensa Uki; Abdonia W. Finmeta, Maya F Roman (ADISAM PUBLISHER, 2025)
In general, mung bean plants in the farming system are only an intercropping crop so that planting is done in the second or third planting season during the rainy season. Shade treatment on mung bean plants, for example netting/paranet used as shade on mung bean plants. The shade provided and received greatly determines the response of mung beans to growth and production. The method used in this research is the Randomised Group Design (RAK), testing is done through 2 stages, namely: anova variance analysis, and the smallest real difference test (BNT) with 5 samples of mung bean plants per treatment, with 3 replications, so that the total observation unit is 15 plants. The results showed that the control plants or without shade (P0) showed the results of plant height, number of leaves, number of pods, number of seeds, and kring weight, which were better than plants with 60% shade treatment (P1), and plants with 80% shade treatment (P2)